The Specificity of Preparing Students at Pedagogical Universities for Educational Activity in the Digital Epoch - Petrenko, Oksana B.; Tsipan, Tetiana S.; Stelmashuk, Zhanna H.; Hrynkova, Nadiia M.; Balika, Liudmyla M. (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Objective: the study is aimed at analysing the problems of forming the skills of educational activities of an individual, leading approaches that outline the range of solutions to education problems, features, and possibilities of these approaches to elucidate the totality of effective methods and techniques for special education pedagogical specialties in students. Background: education in higher education institutions (HEI) or another educational institution is based on the formation of an individual who has achieved the basic characteristics of his development in the process of professional development and in the framework of cooperation. Method: the experimental method was used in work during 2014-2019, in which 219 students of experimental groups and 213 students of control groups participated. Results: The authors determined the possibility of using student training tools as a specialist and a socially responsible person using pedagogical tools implemented in a digital educational environment. Conclusion: Students can be trained in pedagogical higher education directly using digital technologies. Thus, working with similar technologies will not require additional training in the implementation of practical work in further professional activities